STUDIES ON BOVINE TRAUMATIC RETICULO- PERITONITIS IN BAGHDAD - A. YASS, A.; Q. HASSAN, I.; SH. SULTAN , A. (The Iraqi Journal of Veterinary Medicine, 2022)
A total of fourty-five cases of traumatic- reticulo- peritonitis in cows (16 cows ill for 24-48 hrs and 29 cows ill for 72-120 hrs). in Baghdad were diagnosed clinically, laboratory and autopical findings. The most valuable diagnostic signs were increased rectal temperature (39.9 C), respiratory rates (36/min.) and heart beats (95/min.), decreased in milk production (100.00 %), ruminal atony (95.56%), abdominal pain (93.33%), disturbed appetite (91.11%), decrease manure production (84.44%) and recurrent tympany (84. 44%). The total and differential leucocyte counts provided good diagnostic and prognostic data. The determination of total plasma protein and fibrinogen were used as aids to the diagnosis of traumatic reticulo-peritonitis in this study.